Molecular confirmation of the presence of the South American tomato leafminer, Phthorimaea absoluta Meyrick, 1917 (Lepidoptera: Gelechiidae) in Lao PDR - Viengvilay Vorlachith; Sengphet Phanthavong; Somkhit Sengsay; Salah Hafidi; Hang Thi Dao; Chanthason Vongtharone; Bouasa Xaisongkham; Kitan Sitthisay; George A. C. Beattie; Paul Holford; Tara Garrard; Sally Cowan; et al. (Entomological Communications, 2024)
Molecular confirmation of the presence of the tomato leafminer, Phthorimaea (Tuta) absoluta Meyrick, 1917 (Lepidoptera: Gelechiidae), in the Paksong region of the Bolaven Plateau in Champasak province in south-western Lao PDR is reported. The moth, which is native to South America, has invaded many countries in Europe, Africa, and Asia since 2006, and, based on regional records possibly entered Lao PDR between 2014 and 2018. It is a devastating pest of solanaceous crops and threatens tomato production worldwide. Further surveys are required to determine its presence in other regions of Lao PDR and effective management programs must be developed to help farmers minimise losses.